High-Resolution X-Ray Techniques as New Tool to Investigate the 3D Vascularization of Engineered-Bone Tissue - Bukreeva, Inna; Fratini, Michela; Campi, Gaetano; Pelliccia, Daniele; Spanò, Raffaele; Tromba, Giuliana; Brun, Francesco; Burghammer, Manfred; Grilli, Marco; Cancedda, Ranieri; Cedola, Alessia; Mastrogiacomo, Maddalena (Frontiers in Bioengineering and Biotechnology, 2015)
The understanding of structure-function relationships in normal and pathologic mammalian tissues is at the basis of tissue engineering (TE) approach for the development of biological substitutes to restore or improve tissue function. In this framework it is interesting to investigate engineered bone tissue, which is formed when porous ceramic constructs are loaded with Bone Marrow Stromal Cells (BMSC) and implanted in vivo. To monitor the relation between bone formation and vascularization, it is important to achieve a detailed imaging and a quantitative description of the complete three-dimensional vascular network in such constructs. Here we used synchrotron X-ray phase contrast micro-tomography to visualize and analyze the three-dimensional micro-vascular networks in bone-engineered constructs, in ectopic bone formation mouse-model. We compared samples seeded with and without BMSC as well as samples differently stained (comprising unstained samples). Thanks to the high quality of the images, we investigated the 3D distribution of both vessels and collagen matrix and we obtained quantitative information for all different sample preparations. We propose our approach as a tool for quantitative studies of angiogenesis in TE and for any other pre-clinical investigations where a quantitative analysis of the vascular network is required.